2019
DOI: 10.12688/f1000research.18223.2
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge management awareness assessment in Nigerian tertiary institutions

Abstract: Background: Knowledge management (KM) is a recipe for increasing performance and promoting innovation in tertiary institutions. However, some scholars argue that the Nigerian educational sector is yet to fully appreciate the importance of KM as their KM awareness level is still low. Since measurement is the basic foundation to accomplish success, this paper assesses the KM awareness level in tertiary institutions of south-west Nigeria. Methods: The study applied a survey method using a closed ended questionnai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
(22 reference statements)
0
2
0
Order By: Relevance
“…Descriptive statistics was applied to count frequency, total, percentage, maximum, and minmum. Tested hypotheses used the Chi Square One Sample and One Way Anova with α = 0.01 and Pobhirun & Pinitsoontorn (2019) and Ogunbanwo et al (2019) reported the socio-demografic data by using descriptive statistics and analysed hypotheses with Chi Square test. The exchange rate of 1 USD was 14,415.25 IDR on 28 March 2021.…”
Section: Methodsmentioning
confidence: 99%
“…Descriptive statistics was applied to count frequency, total, percentage, maximum, and minmum. Tested hypotheses used the Chi Square One Sample and One Way Anova with α = 0.01 and Pobhirun & Pinitsoontorn (2019) and Ogunbanwo et al (2019) reported the socio-demografic data by using descriptive statistics and analysed hypotheses with Chi Square test. The exchange rate of 1 USD was 14,415.25 IDR on 28 March 2021.…”
Section: Methodsmentioning
confidence: 99%
“…There are limited studies on KM in Nigeria. The few available studies on KM related studies in Nigeria have been centred on; mode of knowledge sharing practices in construction firms (Alhaji et al, 2013a), KM practices relationship with the survival and sustenance of construction firms (Onyeagam et al, 2020), project KM practices of civil engineering construction firms (Alhaji et al, 2013b), KM critical success factors in the construction industry (Idris and Kolawole, 2016), and KM practices among construction professionals (Oke et al, 2013), KM practices in telecommunication industry (Suraj and Ajiferuke, 2013), Nigerian universities and other tertiary institutions KM practices and performance (Ogunbanwo et al, 2019;Ohiorenoya and Eboreime, 2014;Ojo, 2016). These studies failed to indicate the size or categorisation of the firms upon which samples were based, especially for those studies carried out in the construction industry.…”
Section: Introductionmentioning
confidence: 99%